The Effectiveness of Using Educational Board Games on Students’ Vocabulary Mastery at Junior High School - Sari, Sinta Kurnia; Ifrianti, Syofnidah; Aryanika, Septa (Lembaga Sosial Rumah Indonesia, 2025)
Purpose – This study investigates the effectiveness of educational board games in enhancing the vocabulary mastery of seventh-grade students at SMPN 24 Bandar Lampung. It aims to determine whether there is a significant difference in vocabulary achievement between students taught using board games and those taught through conventional instructional methods.Method – The study was conducted during the second semester of the 2024/2025 academic year using a quasi-experimental design with a pre-test–post-test control group. A total of 60 students were selected through purposive sampling, with 30 students in the experimental group and 30 in the control group. The experimental group received vocabulary instruction through educational board games, while the control group was taught using conventional methods. Data were collected using a 50-item multiple-choice vocabulary test and analyzed using an independent samples t-test.Findings – The analysis showed a statistically significant difference in post-test scores between the experimental and control groups, t (58) = 8.575, p < 0.001. The students in the experimental group demonstrated significantly higher vocabulary mastery, with a mean score difference of 15.867 points compared to those in the control group. Research Implications – The results provide empirical support for the use of educational board games as an effective and engaging teaching strategy in English language learning. These games offer a structured yet enjoyable approach to vocabulary acquisition, which can enhance students' comprehension and retention of English vocabulary.